Preparation and thermal characteristics of eutectic fatty acids/Shorea javanica composite for thermal energy storage - Fauzi H.; Metselaar H.S.C.; Mahlia T.M.I.; Chyuan Ong H.; Nasruddin; Khanlou H.M. (Elsevier Ltd, 2023)
Chemical analysis; Chemical stability; Differential scanning calorimetry; Eutectics; Fatty acids; Heat storage; Nobelium; Palmitic acid; Phase change materials; Porous materials; Saturated fatty acids; Thermoanalysis; Thermodynamic properties; Thermodynamic stability; Chemical compatibility; Composite phase change materials; Conductivity analysis; Fatty acid eutectics; Fourier transform infra reds; Impregnation methods; Thermal characteristics; Thermal Performance; Thermal conductivity